The morphological trigger of V-to-T: The case of Old English - Castillo, Concha (Adam Mickiewicz University, 2016)
This paper deals with the phenomenon of V-to-T movement, which is one of the major parameters differentiating Romance from the majority of modern Germanic languages, and it defends the idea that rich morphology is the cause or trigger of V-to-T: in Romance, in a modern Germanic language like Icelandic, and very particularly in Old English, the precursor of the modern English language. More generally, the discussion endorses the idea that all Germanic languages used to be V-to-T languages in their old periods. I begin by arguing that verbal forms in Spanish contain a specific kind of segment, namely the stem or thematic vowel, which gives rise to morphological variations or asymmetries across tenses in the language. Such a productive system of stem verb classes is also shown to be the case in Icelandic, though not in German (which is therefore rendered as non-V-to- T), and ultimately it is acknowledged for a language like OE. The hypothesis is that the syntactic computation of (OE) verbal forms demands it that the speaker first identifies the verb class that the form in question belongs to before tackling the processing of tense morphology and agreement morphology. In pure syntactic terms, the stem or thematic vowel segment is identified in the present account with a v-feature that T must value, which valuation is realised by means of the displacement of the verb to the T head, that is, by means of V-to-T movement. After the valuation of T’s v-feature comes the valuation of τ–features and φ–features, respectively.
Keywords: V-to-T movement; Romance; Icelandic; German; Old English; old Germanic languages; stem or thematic vowel; T’s v-feature; τ–features; φ–features